Model Pembelajaran Problem Based Learning sebagai Implementasi Aliran Konstruktivisme Pada Pembelajaran Sejarah - Abdilah Farid Rifki; Yulianti Yulianti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
The learning pattern developed today is the student center. The emergence of a model of learning problem based learning is also a suggestion for developing that learning pattern. In the model of learning problem based learning all learning processes are centered on students. The teacher only functions as a facilitator that helps students accomplish the prescribed learning purpose before the learning begins. Researchers see an implementation of a school of constructive flows on a model based learning problem. The context discussed is history learning. Based learning model based learning asan implementation of a constructive stream on history study. This discussion uses a library study method that is through books and journals.